Response Guidelines for Newborn Infants Born to Mothers with Suspected or Confirmed Coronavirus Disease 2019 - Do-Hyun Kim (Korean Society of Neonatology, 2020)
Since December 2019, the coronavirus disease 2019 (COVID-19) has been spreading rapidly worldwide. With the increase in the number of infections, the numbers of pregnant women and newborn infants with COVID-19 are also increasing. Accord ing to the limited recent studies, COVID-19 appears to be mainly transmitted to newborn infants by the mother's droplets or direct contact with the mother, and no clear evidence supports the vertical transmission from the mother to the newborn infant. To date, the likelihood of severe outcomes in newborn infants born to mothers with confirmed COVID-19 is relatively very low, but the possibility should be considered. The present response guidelines address the management of newborn infants born to mothers with suspected or confirmed COVID-19. The management covers precautions for birth attendants or medical staffs, testing for COVID-19, isolation, neonatal care, breastfeeding, and mother/baby contact. These response guidelines can be revised in accordance with further updates on COVID-19 and should be adapted to each local health-care facility.